Genomic and Proteomic Analyses of Salmonella enterica Serovar Enteritidis Identifying Mechanisms of Induced de novo Tolerance to Ceftiofur - Radford, Devon; Strange, Philip; Lepp, Dion; Hernandez, Marta; Rehman, Muhammad Attiq; Diarra, Moussa Sory; Balamurugan, S. (Frontiers in Microbiology, 2018)
With the alarming proliferation of antibiotic resistance, it is important to understand the de novo development of bacterial adaptation to antibiotics in formerly susceptible lineages, in the absence of external genetic input from existing resistance pools. A strain of ceftiofur susceptible Salmonella enterica serovar Enteritidis ABB07-SB3071 (MIC = 1.0 µg/ml) was successively exposed to sub-MIC of ceftiofur to allow its adaptation for tolerance to a concentration of 2.0 µg/ml of this antibiotic. Genomic and proteomic comparative analyses of the parental strain and induced tolerant derived lineages were performed to characterise underlying mechanisms of de novo adaptation (tolerance). Expression and localization of specific drug-, heme-, sugar-, amino acid-, and sulfate-transporters were altered, as was the localization of the cell membrane stabilizing protein OsmY in the tolerant strains adapted to 2.0 µg/ml compared to the parental isolate lines. This redistribution of existing transporters acts to minimize the concentrations of ceftiofur in the periplasm, by decreasing facilitated import and increasing active efflux and cytosolic sequestration as determined by HPLC quantification of residual total and extracellular ceftiofur after growth. Genetic, subcellular localization, and abundance changes of specific regulators of transcription, translation, and post-translational dynamics in the derived ceftiofur tolerant lineages decrease metabolic strain on cell walls and enhance periplasmic envelop stability against stress. This produces slower growing, more tolerant populations, which deplete free ceftiofur concentrations significantly more than susceptible parental populations (P <0.05), as measured by recoverable levels of ceftiofur from cultures of equivalent cellular density incubated with equal ceftiofur concentrations. Genetic and abundance changes to specific carbon and nitrogen metabolism enzymes, not traditionally associated with beta-lactam metabolism, establish an enzymatic framework with the potential to detoxify/degrade ceftiofur, while mutations and changes in subcellular localization in specific cell surface factors enhances the stability of the Gram-negative cell envelop despite the compromising effect of ceftiofur. The observed changes highlight generalizable mechanisms of de novo tolerance without horizontal gene transfer, and thus can inform policies to combat antibiotic tolerance and minimize induction of de novo tolerance.